Quality of life and medication adherence in patients with chronic heart failure associated with arterial hypertension and chronic kidney disease - Khaniukov, Oleksii; Smolianova, Oleksandra (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
As a permanent blockage of the pathogenetic chains of the disease prevents its progression and decompensation, medication adherence remains a cornerstone in the management of chronic heart failure. Poor adherence leads to an increase in chronic heart failure manifestations and frequent hospitalizations, resulting in quality of life deterioration. Aim. To characterize the quality of life in the elderly with chronic heart failure with preserved ejection fraction on the background of arterial hypertension and chronic kidney disease, and to determine the effect of medication adherence on the quality of life. Materials and methods. The prospective study included 122 patients aged 64 [62; 68] years with chronic heart failure on the background of arterial hypertension and chronic kidney disease. All participants underwent a clinical examination, a creatinine level determination with subsequent calculation of GFR EPI, a 6-minute walk test, an assessment according to the Minnesota Living with Heart Failure Questionnaire, and the Morisky Green Medication Adherence Scale. Based on the medication adherence level, the participants were divided into 2 groups. Results. Patients in both groups were comparable in age, sex, and ejection fraction. The patients in the non-adherent cohort had more comorbid diseases, greater systolic blood pressure and functional class according to NYHA, higher heart rate, a larger percentage of patients with lung crackles and GFR EPI less than 60 ml/min/1.73m2, lower GFR EPI, the shorter distance at 6-minute walk test, and the worse quality of life. The the quality of life was (the first figure – during hospitalization, the second - after 6 months, the third - after 12 months): 50 [39; 61], 42 [31; 50] and 40 [29; 50] scores among all the patients; 58.5 [48; 62], 47 [42; 52] and 47.5 [38; 54] scores – among non-adherent cohort; 41 [35, 53], 30 [28; 40] is the 29 [27; 40] scores - among the adherent patients. Conclusion. The quality of life of non-adherent patients was significantly worse in comparison with those who were more adherent to therapy. This difference was observed during both hospitalization and repeated outpatient observations. Medication adherence remained a significant quality of life predictor at all three visits: worsening in adherence level resulted in a quality of life deterioration. As the mediators causing the connection between medication adherence and the quality of life were patients’ characteristics indicating poor diseases compensation.